(untitled) (Journal of Oriental Studies, 2024)
The policy of the People’s Republic of Azerbaijan towards the Kurds has been a controversial issue for decades and has generated widespread debate, dating back to the early years of Soviet reign in Azerbaijan. The Soviet government, which first established its presence in Azerbaijan in the early 1920s, pursued a policy of resettlement and assimilation of indigenous peoples and ethnic minorities, such as the Kurds, who historically lived in border regions with Iran and Turkey. As part of this policy, which continued throughout the Soviet years, the government forcibly resettled thousands of Kurds to other parts of southern Azerbaijan, away from their traditional homeland, as part of a broader initiative to create ethnically homogeneous regions. This process caused significant social and economic upheaval for many Kurdish communities and led to widespread opposition and resistance. Since gaining independence from the Soviet Union in 1991, Azerbaijan has pursued a more multifaceted policy towards the Kurds, seeking to balance its territorial claims and security interests with the rights and needs of the Kurdish population. While Azerbaijan officially “recognizes” the presence of Kurds within its borders and has spoken in recent years of granting some cultural and linguistic rights to Kurdish communities, at the same time, it took a tough stance against the activities of Kurdish political movements and activists who, in its thought, pose a threat to the territorial integrity of the state.